Lizard on the wall appearance-total laparoscopic hysterectomy on a ventrofixed uterus - Dhandapani, Kalyani Sai; Karthikeyan, Sadhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Hysterectomy is one of the most performed procedures for gynecological conditions worldwide. Ventrofixation of the uterus, a surgical technique where the uterus is fixed to the anterior abdominal wall, can complicate routine gynecological procedures, including hysterectomy. Performing a total laparoscopic hysterectomy (TLH) on a ventrofixed uterus presents unique challenges due to altered anatomy and the presence of adhesive tissues. Adhesions during surgery are associated with increased morbidity due to prolonged operating time and organs injuries. A ventrofixed uterus can often be suspected in patients with a history of CS, based on specific clinical symptoms and ultrasonographic findings described by Sheth et al. Surgeons should be aware of the altered anatomy and the potential for adhesions when performing laparoscopic hysterectomy in such cases. Appropriate preoperative workup and planning of surgery reduces complications and improves the outcome. Some of techniques for dissection of ventrofixed uterus is discussed in this paper.